2012
DOI: 10.1097/opx.0b013e3182357f79
|View full text |Cite
|
Sign up to set email alerts
|

Myopia Progression Rates in Urban Children Wearing Single-Vision Spectacles

Abstract: Purpose To conduct a meta-analysis on the rates of myopia progression in urban children of Asian and predominately European ethnicities who are corrected with traditional single-vision spectacles. Methods A search of the National Library of Medicine’s PubMed literature database for articles on myopia progression was conducted using the terms ‘myopi*progression’ and MeSH terms ‘myopia’ and ‘disease progression’, and limited to publications from January 1990 and only for papers reporting data for humans < 16 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
157
5
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(176 citation statements)
references
References 45 publications
7
157
5
7
Order By: Relevance
“…Two independent research groups, using genome-wide association studies, have identified 20 genetic loci that have been linked to myopia [7]. Environmental factors such as long periods of near work, type of optical correction, and limited outdoor time also affect myopia development [8][9][10][11]. One study reported that increasing time spent outdoors can delay the onset of myopia [12].…”
Section: Introductionmentioning
confidence: 99%
“…Two independent research groups, using genome-wide association studies, have identified 20 genetic loci that have been linked to myopia [7]. Environmental factors such as long periods of near work, type of optical correction, and limited outdoor time also affect myopia development [8][9][10][11]. One study reported that increasing time spent outdoors can delay the onset of myopia [12].…”
Section: Introductionmentioning
confidence: 99%
“…This is not unexpected given that myopia in children tends to progress with age (Donovan et al 2012) and hence become greater in magnitude with time. Three of four binocular vision measures showed significant change from single vision spectacle to OK wear in this study, and each of these measures showed strong interrelationship with the others on partial correlations.…”
Section: The Effect Of Age and Frequency Of Bv Disordersmentioning
confidence: 75%
“…In adults, lower baseline myopia was correlated with a lower (less accurate) tonic accommodation measure (Chapter 5), with these lower myopes also showing the biggest improvements in divergence (BIFR -Chapter 4) in OK wear. As previously discussed in Chapter 4, in both cases this is likely related to time of myopia progression -higher myopia in children is likely associated with myopia progression (Donovan et al 2012) while in adults, late-onset myopia generally results in a lower refractive error than early-onset. (Grosvenor 1987, Bullimore et al 1992 Late-onset myopes have been shown to have reduced accommodative function compared emmetropes and early-onset myopes, , McBrien and Millodot 1988, Rosenfield and Gilmartin 1990 …”
Section: Binocular Vision and Level Of Myopiamentioning
confidence: 89%
See 2 more Smart Citations